2019
DOI: 10.1002/cncy.22206
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐derived cell‐free DNA in body cavity effusion supernatants: A promising alternative for genomic profiling

Abstract: In an era of precision medicine, liquid biopsy using plasma derived cell-free DNA (cfDNA) provides a noninvasive option for tumor genomic profiling in patients with advanced stage malignancies. 1,2 Although liquid biopsy assays using plasma-based cfDNA have gained popularity for detecting tumor evolution and monitoring minimal residual disease, genomic profiling using tumor-derived cfDNA from other specimen sources such as cerebrospinal fluids, urine, body cavity effusions, and fine needle aspiration supernata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In addition, cell-free DNA analysis is a promising strategy to evaluate targetable mutations in malignant effusions, particularly in cases with pulmonary adenocarcinoma. [32][33][34] By using deep sequencing of cell-free DNA in effusion supernatant, Yang et al even found pathogenic alterations in one benign cytology sample from a patient with metastatic cancer. 32 The advancement and popularity of highly sensitive molecular tests may help detect tumors and provide therapeutic or prognostic genotypes.…”
Section: Pericardialmentioning
confidence: 99%
“…In addition, cell-free DNA analysis is a promising strategy to evaluate targetable mutations in malignant effusions, particularly in cases with pulmonary adenocarcinoma. [32][33][34] By using deep sequencing of cell-free DNA in effusion supernatant, Yang et al even found pathogenic alterations in one benign cytology sample from a patient with metastatic cancer. 32 The advancement and popularity of highly sensitive molecular tests may help detect tumors and provide therapeutic or prognostic genotypes.…”
Section: Pericardialmentioning
confidence: 99%
“…In previous studies, a handful of variants detected by NGS performed on DNA extracted from FFPE were not detected by NGS performed on ES (19,25,37). Accordingly, while the paradigm may be shifting (8), nucleic acid extracted from FFPE tissue sections remains the current gold standard substrate for clinical NGS. In the current study, one pathogenic variant was identified upon sequencing of FFPE (the presumptive primary lung mass) but not from a corresponding PES of low TC containing predominantly high molecular weight DNA.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…Plasmabased testing allows for serial sampling and less artifact from chemical processing and a more accurate representation of tumor heterogeneity and evolution than for traditional FFPE tissue (5)(6)(7). More recently, tumor-derived cfDNA from other specimen types, including cerebrospinal fluid, urine, serous effusion fluid, and fine needle aspiration (FNA) supernatant has also been sequenced with favorable results (8)(9)(10)(11)(12)(13)(14)(15). Effusion fluid, in particular, is enriched in cfDNA species, making it a perfect medium for molecular testing (12,(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…26 In addition to plasma-based testing, there are a wide variety of other cytology liquid samples, including urine, sputum, cerebrospinal fluid (CSF), effusions, and fine-needle aspiration (FNA) supernatant fluids that have been explored for their potential role in tumor molecular profiling and the dynamic monitoring of drug resistance. [27][28][29][30] However, the majority of these unconventional liquid biopsies currently are not offered in a reference laboratory setting and have been explored largely in academic settings with access to in-house molecular testing capabilities that allow for the additional validation needed for these assays. Some of these other liquid biopsy options and their role in NSCLC biomarker testing are discussed below.…”
Section: The Liquid Biopsy: a Variety Of Liquid Specimen Typesmentioning
confidence: 99%
“…One of the alternate, more readily accessible liquid biopsy sources that has been exploited for molecular profiling is ctDNA obtained from serous body cavity effusion fluids. 30,46 A large percentage of patients with advanced stage NSCLC initially present with a malignant pleural effusion that may be the only tissue source for diagnosis and biomarker testing. Recent studies evaluating the cellfree component of these samples for tumor mutational profiling have highlighted the role of centrifuged supernatant fluids from these effusion samples in providing clinically relevant genomic information for primary driver mutations as well as those in a resistance setting.…”
Section: Pleural Effusion and Ascitic Fluidmentioning
confidence: 99%